The Importance of E-Crm on PLN Mobile Applications to Increase E-Customer Loyalty by Improving E-Service Quality and E-Customer Satisfaction - Revda, Afdilla (JURNAL PENELITIAN PENDIDIKAN, PSIKOLOGI DAN KESEHATAN (J-P3K), 2025)
PT Perusahaan Listrik Negara (Persero) or PLN, is an Indonesian State-Owned Enterprise engaged in the electricity sector for the provision of electrical energy in Indonesia. As one of the strategic companies in the energy sector, PLN has an important role in supporting economic growth throughout Indonesia as its customers. To improve operational efficiency and provide a better experience to customers, PLN continues to innovate through digital technology, namely by launching the PLN Mobile application designed to facilitate customers. In the context of service digitalization, the implementation of E-CRM and improving E-Service Quality are PLN's strategic priorities. This research was provided by 255 respondents by filling out a questionnaire in the form of a google form from August to October by users of the PLN Mobile application in Banten Province. The data was processed with the data analysis method used to test the validity and reliability using is Structural Equation Modeling (SEM) PLS.  Through this strategy, PLN aims to increase E-Customer Satisfaction and E-Customer Loyalty which ultimately supports the company's business sustainability. This study aims to analyze the effect of E-CRM and E-Service Quality on E-Customer Satisfaction and E-loyalty in the PLN Mobile application, as an effort to understand the effectiveness of the company's digital strategy in providing optimal service to customers.